TCP/IP sockets in Java practical guide for programmers - Calvert, Kenneth L.; Donahoo, Michael J. (San Francisco : Morgan Kaufmann Publishers, 2002)
Most Internet applications use sockets to implement network communication protocols. TCP/IP Sockets in Java: Practical Guide for Programmers, with its focused, tutorial-based coverage, helps you master the tasks and techniques essential to virtually all client-server projects using sockets in Java. Later chapters teach you to implement more specialized functionality; incisive discussions of programming constructs and protocol implementations equip you with a deeper understanding that is invaluable for meeting future challenges. No other resource presents so concisely or so effectively the exact material you need to get up and running with Java sockets programming right away. For those who program using the C language, be sure to check out this book's companion, TCP/IP Sockets in C: Practical Guide for Programmers. For example code from the text, sample programming exercises, Powerpoint slides, and more, click on the grey "Companion Site" button to the right. *Concise, no-nonsense explanations of issues often troublesome for students, including message construction and parsing, underlying mechanisms and Java I/O *Comprehensive example-based coverage of the most important TCP/IP techniques-including iterative and threaded servers, timeouts and asynchronous message processing *Includes a detailed, easy-to-use reference to the relevant JAVA class libraries *A companion Web site provides online code for all the example programs given in the book *Provides a guide to common errors and a reference offering detailed documentation of the sockets interface *Perfect for a practitioner who may even want just to "look into" this technology. *Provides tutorial-based instuction in key sockets programming techniques, focusing exclusively on Jva and complemented by example code. *Covers challenging sockets programming issues: message construction and parsing, underlying TCP/IP protocol mechanisms, Java I/O, iterate and threaded servers, and timeouts. *Includes references to the relevant Java class libraries that often go beyond the "official" Java documentation in clarity and explanation. *Provides code for all example programs, along with additional exercises, via companion Web site.
Chapter 1 Introduction -- Chapter 2 Basic Sockets -- Chapter 3 Sending and Receiving Messages -- Chapter 4 Beyond the Basics -- Chapter 5 Under The Hood.
Includes bibliographical references and index.
Keywords: Internet programming; TCP/IP (Computer network protocol); Java (Computer program language).; Electronic books